THE ROLE OF TEACHERS IN INSTALLING THE VALUES OF TOLERANCE IN EARLY CHILDREN - Ghanimah, Ghanimah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
One of the character values that is instilled in children is tolerance. Instilling the value of tolerance from an early age aims to ensure that children have a sense of respect for diversity. The aim of this research is to explain the importance of the role of teachers in instilling the value of tolerance in early childhood at Raudatul Athfal Miftahul Ulum. This research method involves classroom observations, interviews with teachers and analysis of curriculum documents. The collected data was analyzed qualitatively to identify teacher behavior patterns in designing understanding and acceptance of diversity. The results of the research show that the role of teachers in instilling the value of tolerance in children includes designing a tolerance curriculum, having optimal and proportional competence and having a strong commitment to providing examples to children regarding character values, one of which is the value of tolerance. The teacher's role in instilling the value of tolerance can also be through learning activities using several methods such as providing role models, providing direction, habituation, involving stories, role playing and collaborative activities, storytelling activities, game activities and the use of media, proven to be effective in increasing understanding and understanding. tolerance attitude. Apart from teachers, parents, the community also plays an important role in instilling the values of tolerance because young children also live in a pluralistic society.